Branchial, renal and hepatic lesions in an estuarine mullet, Liza parsia Hamilton - Buchanan, induced by sublethal exposure to BHC - Pandey, A K; George, K C; Peer Mohamed, M (Indian Journal of Fisheries, 2011)
Gill of Liza parsia exposed to sublethal concentration (0.5 ppm) of BHC responded initially with the copious secretion of mucus followed by oedematous separation of epithelial lining cells from the basement membrane. Fusion of secondary gill lamellae, tissue hyperplasia and multiple telangiectases (aneurysms) were noticed on day 10 of the exposure. By day 15, the entire interlamellar spaces became filled with the hyperplastic epithelium. Kidney revealed an initial hypertrophy of the cells lining proximal convoluted tubules followed by shrinkage in the glomerular tufts resulting in the increase of Bowman's space and oedema. Tubulonecrosis, hyperemia and fibrosis were noticed in the reneal tissue after day 19 of BHC intoxication. Exposure to BHC elicited an initial dilation of bile canaliculi, enhanced secretion of bile and cellular hypertophy on day 4. Necrotic changes like excessive vacuolation, and karyorrhexis and karyolysis were seen on day 8. By day 10 and 15, complete vacuolation of hepatocytes, pycnosis of nuclei and focal necrosis were noticed.